Karstology and speleology in Slovenia - Kranjc, Andrej (Annales. Series historia naturalis, 1997)
The article presents briefly the development of the term "karst", karstology and speleology in Slovenia, with an emphasis on the achievements of Slovene researchers and response to them elsewhere in the world. Since the second World War, the Slovene karstologists have played increasingly active part on the international karstologic scene. The author of the article believes that the future of a successful affirmation of our karstology lies in a detailed introduction of karstology to higher education, and in active participation inthe attempts to solve the issues concerning everyday life and economy on the karst.
Keywords: karst; Kras; krasoslovje; Slovenia; Slovenija; speleologija; zgodovinski pregledi